Sensitive Detection of Single-Nucleotide Polymorphisms by Solid Nanopores Integrated With DNA Probed Nanoparticles - Wu, Ling Zhi; Ye, Yuan; Wang, Zhi Xuan; Ma, Die; Li, Li; Xi, Guo Hao; Bao, Bi Qing; Weng, Li Xing (Frontiers in Bioengineering and Biotechnology, 2021)
Single-nucleotide polymorphisms (SNPs) are the abundant forms of genetic variations, which are closely associated with serious genetic and inherited diseases, even cancers. Here, a novel SNP detection assay has been developed for single-nucleotide discrimination by nanopore sensing platform with DNA probed Au nanoparticles as transport carriers. The SNP of p53 gene mutation in gastric cancer has been successfully detected in the femtomolar concentration by nanopore sensing. The robust biosensing strategy offers a way for solid nanopore sensors integrated with varied nanoparticles to achieve single-nucleotide distinction with high sensitivity and spatial resolution, which promises tremendous potential applications of nanopore sensing for early diagnosis and disease prevention in the near future.